Effect of Oral Health Mobile App on Child's Brushing Efficacy - A/Prof Kalpana Bansal; Dr Bharathi Purohi; Dr Harsh Priya; Dr Azeema Shamoo; Dr Vijay Mathur (Elsevier, 2023)
Aim or Purpose: In this era of digital technology, mobile apps have found their utility in several aspects of managing peoples' own health and wellness. The purpose of this study was to evaluate the effectiveness of an oral health mobile application on the brushing efficacy of children and knowledge of parents. Materials and Methods: A prior approval was obtained from institutional ethics committee to carry out this study (Ethics approval number-IEC-1139/06.11.2020). Two to ten years old, child-parent dyads (n=52) were recruited from the hospital setting. Children's oral hygiene was evaluated using the Plaque Index; while parents were assessed for the knowledge about oral health using a validated operator-administered self-structured questionnaire. "Healthy- Smile Swasth-Muskaan" mobile application was installed in their android phones and participants were taught to use the application on a regular basis. After one month of the installation of the app, child's oral hygiene and parents' knowledge was re-evaluated. Paired t test was used to evaluate change in plaque score after app installation while McNemar's test was used to assess change in responses to knowledge questions. A p<0.05 was considered statistically significant. Results: At one month follow-up, a significant reduction occurred in the mean plaque scores of the children from 1.6± 0.32 to 0.94± 0.45 (p<0.001). A significant improvement occurred in the percentage of correct responses from parents about oral health maintenance after app installation in their phones (p< 0.001). Conclusions: Brushing efficacy of the children improved significantly after following the mobile application. The app was effective in improving the oral health knowledge of the parents.